Impact of heart disease on hand grip strength in COPD: epidemiological data - Johansson Strandkvist, Viktor; Backman, Helena; Röding, Jenny; Stridsman, Caroline; Lindberg, Anne (Luleå tekniska universitet, Hälsa och rehabilitering, 2016)
Background: Hand grip strength (HGS) and heart disease (HD) are related to mortality. Peripheral muscle dysfunction and HD are both frequently observed among subjects with COPD, but the relationship between HGS and HD in COPD is unclear. Aim: To evaluate HGS and the impact of HD among subjects with and without COPD.Methods: Data was collected from the OLIN (Obstructive Lung Disease in Northern Sweden) COPD study, where subjects with COPD have been invited to annual examinations since 2005 together with age- and sex-matched subjects without COPD. During 2009, 441 subjects with COPD and 570 without COPD participated in examinations including structured interviews, spirometry and measurements of HGS. COPD was defined as post-bronchodilator FEV1/VC<0.70. Results: Both among subjects with and without COPD, and in both sexes, those with HD had significantly lower HGS. The proportion of subjects below estimated normal value for HGS was similar in subjects with and without COPD and in both sexes; among women (35.4 vs. 33.4%, p=0.714) and men (19.1 vs 15.9%, p=0.315). In a linear regression model among subjects with COPD only, HGS was significantly associated with age, beta coefficient (B) = -0.46 (p<0.001), sex, B=19.85 (p<0.001) and FEV1 % of predicted normal value, B=0.06 (p=0.007), but not with HD or smoking habits. When a similar model was estimated among subjects without COPD, HGS was only associated with age and sex. Conclusions: In this population-based study, subjects with heart disease had lower hand grip strength regardless if they had COPD or not. Among COPD subjects, hand grip strength was associated with age, sex and FEV1, but not with heart disease.